A educação feminina no projeto siqueirano: 1939-1973 - Neves, Gislene Taveira de Almeida (2005)
This work is part of the research of the Master s Degree in Education program from the Federal University of Uberlândia/MG and has as its primary objective to know, analyze and register the paths taken in the construction of the Nossa Senhora do Amparo high school, built in the city of Monte Carmelo, in the year of 1939 under the direction of the Franciscan Sisters of Nossa Senhora do Amparo, paying special attention to the issue of feminine education. This research is set between the tears of 1939 and 1973, taking into consideration that, in the 70 s, the Normal Course curriculum received the subjects of the then called Scientific Course, as a consequence of the alterations brought forth by Law 5.692/71 of the 1º and 2º degree education reform, after which it became known as Normal High School. This approach will be made by highlighting the macro history context in which this catholic confessional school inserts itself, allowing therefore the possibility of thinking of it as an educational space where women students and nuns re-create unique and multiple ways of thinking and behaviors, among the appropriations that highlight peculiar and relevant hues for the historical construction of Brazilian education. The theoretical-methodological support for this research was obtained in the propositions of the New Cultural History, under the perspective of the approaches proposed by Roger Chartier, seeing as possible to think history from the point of view of social representations, which articulate themselves as mechanisms forged in the interior of relations permeated by clashes, in the practice of social subjects who manifest themselves in the acceptance/re-elaboration or rejection/resistance to the roles which are in many ways imposed or offered as adequate or convenient. By interviewing the big and the little , it is intended to rescue the details of a history that is built between signals and readings of a past that always provokes a new look, a new path along the ways of historical research of Brazilian education.